Chronic illness experience in the context of resource-limited settings: a concept analysis - Ellen Samwiri Nkambule; Gladys Msiska (International Journal of Qualitative Studies on Health & Well-Being)
Aim This review describes the ways in which individuals experience chronic illnesses in resource-limited settings; to define the concept and understand its attributes, antecedents and consequences. Methods A comprehensive analysis of the databases CINAHL, PubMed and Google Scholar was conducted. During literature search the following limits were applied: articles published in English with available full-text; articles that focused on living with chronic illness in adults from the patient’s perspective. Results The following three attributes of chronic illness experience were identified: transformational experience, acceptance and self-management. Prominent predisposing factors (antecedents) were: genetic inheritance, malnutrition and poverty, high levels of stress and unhealthy lifestyle. The most dominant consequences were as follows: impact on quality of life; self-management burden; burden to others and economic stressors. Conclusions The findings underscore the need for health-care professionals to understand the chronic illness experience in the context of resource-limited settings and its consequences. The greater insights into the concept of chronic illness experience in resource-limited settings will guide nurses to support people in the realities of chronic illness experience in resource-limited settings in developing countries. This knowledge can guide nurses in providing competent care to chronically ill individuals, including meeting their individual needs with such illnesses.